PERTALIAN TRADISI KERIS TANGGUH NGÃNTHA-ÃNTA YOGYAKARTA: Titik Awal dan Kebangkitan Historis - Timbul Haryono, Supriaswoto dan (CORAK, 2012)
Kerris is stabbing weapon for the archipelago wich have a term of religious, values, magical, aesthetic, and mysterious, but also have a politic value, economy, sociology, and art that not timeless. It prove that kerris existence still exists and continuous to exists. The one that get tracked is Tangguh Ngentha-entha Kerris of Yagyakarta. Who masters that become the supportersand how Tangguh Ngentha-entha Kerris rise back and found their identifycan be listened to in the following text.Keyword : Kerris, Tangguh Ngentha-entha, empu, Entha Wayang.